'Race', ethnicity and whiteness in the governance of the events industry. Issue 2 (4th May 2018) - Fletcher, Thomas; Hylton, Kevin
ABSTRACT: In a recent policy debate in this journal, focusing on gender and the events industry, Rhodri Thomas states that his intention in writing the piece was to challenge policy-makers and those working in representative organisations related to events to take equalities more seriously. The aim of this paper is to both react to this call and to make a similar one, explicitly challenging the need for more policy considerations and research into 'race', ethnicity and whiteness in the context of the events industry. While the notion of social justice is receiving greater scrutiny in the event literature, ideas of 'race', ethnicity and their intersections, and whiteness are neither currently addressed nor understood. Many of the privileges afforded by whiteness processes rely on its reported invisibility, hegemony and supremacy. The first step in combating these privileges and their effects, is in explicitly identifying whiteness and making it visible. A simple acknowledgement that the lack of Black and minoritised ethnic people on the Boards of events organisations, is a good starting point, but alone, this is not enough. If the commitment to racial equality is to be more than a form of paying lip-service, then it is also necessary to engage with the deep-rooted cultural relations of power that sustain racially exclusive practices. If not addressed, the disproportionate number of leadership positions in events organisations will continue to perpetuate the 'snowy white peaks' of the industry's representative bodies.